Effects of Fracture Connectivity on Rayleigh Wave Dispersion - Quiroga, Gabriel E. (2022)
Passive seismic characterization is an environmentally friendly method to estimate the seismic properties of the subsurface. Among its applications, we find the monitoring of geothermal reservoirs. One key characteristic to ensure a productive management of these reservoirs is the degree of fracture connectivity and its evolution, as it affects the flow of fluids within the formation. In this work, we explore the effects of fracture connectivity on Rayleigh wave velocity dispersion accounting for wave-induced fluid pressure diffusion (FPD) effects. To this end, we consider a stratified reservoir model with a fractured water-bearing formation. For the stochastic fracture network prevailing in this formation, we consider varying levels of fracture density and connectivity. A numerical upscaling procedure that accounts for FPD effects is employed to determine the corresponding body wave velocities. We use a Monte-Carlo-type approach to obtain these velocities and incorporate them in the considered fractured reservoir model to assess the sensitivity of Rayleigh wave velocity dispersion to fracture connectivity. Our results show that Rayleigh wave phase and group velocities exhibit a significant sensitivity to the degree of fracture connectivity, which is mainly due to a reduction of the stiffening effect of the fluid residing in connected fractures in response to wave-induced FPD. These effects cannot be accounted for by classical elastic approaches. This suggests that Rayleigh wave velocity changes, which are commonly associated with changes in fracture density, may also be related to changes in interconnectivity of pre-existing or newly generated fractures.